2011
DOI: 10.1002/cae.20576
|View full text |Cite
|
Sign up to set email alerts
|

Active learning in robotics based on simulation tools

Abstract: Simulation is a powerful tool that has a very important role in the different areas of research, development, and education. In particular, simulation tools are widely used in robotics. In this article, we present an active learning experience based on simulation tools in the framework of robotics courses taught at engineering degrees. It is well known that the field of robotics involves many disciplines taught in higher education, such as mechanics, electronics, or computer science. In the context of a roboti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…From the author experience (based on discussions with other colleagues teaching similar subjects) hands-on courses on industrial robotics are not frequent due to, mainly, two reasons [6,22]: (i) the cost of industrial robots that makes difficult to equip laboratories with these equipments (a problem common to other countries); (ii) the time needed to program, and test the developed programs, on-line. Since robot programs involve the motion of the robot, they have to be tested at low velocities for safety reasons in order to avoid collisions that may occur due to unwanted motions Third International Conference on Technological Ecosystems for Enhancing Multiculturality -TEEM'15 To overcome these problems faced with traditional courses on robotics, an innovative approach was followed: the practical classes are taught using a simulation software for the simulation and off-line programming of industrial robots.…”
Section: Discussion On the Course Expe-riencementioning
confidence: 98%
See 1 more Smart Citation
“…From the author experience (based on discussions with other colleagues teaching similar subjects) hands-on courses on industrial robotics are not frequent due to, mainly, two reasons [6,22]: (i) the cost of industrial robots that makes difficult to equip laboratories with these equipments (a problem common to other countries); (ii) the time needed to program, and test the developed programs, on-line. Since robot programs involve the motion of the robot, they have to be tested at low velocities for safety reasons in order to avoid collisions that may occur due to unwanted motions Third International Conference on Technological Ecosystems for Enhancing Multiculturality -TEEM'15 To overcome these problems faced with traditional courses on robotics, an innovative approach was followed: the practical classes are taught using a simulation software for the simulation and off-line programming of industrial robots.…”
Section: Discussion On the Course Expe-riencementioning
confidence: 98%
“…Furthermore, in order to disseminate robotics education, some Internet based remote laboratories for teaching robotics have been implemented [14,17,9,6], and several institutions have made available through the internet sites were the user can interact with real robots, either with educational purposes or just for fun [24]. Besides using the internet to disseminate teaching and education, without the inherent costs of hardware, another possibility is the use of simulation applications [14,8,22]. Simulation is a powerful tool playing an important role in different areas of research, development, and education.…”
Section: State Of the Art In Industrial Robotics Educationmentioning
confidence: 99%
“…Rather than studying the forward kinematics of virtual robot models already created, the EjsRL library and ARTE allow students to specify all of the D–H parameters of a chosen robot and associate their model with custom 3D graphics files. Similarly, RobotScene provides a sophisticated GUI in which students can create and assemble 3D virtual robot links according to the D–H parameters that they have determined. These tools require students to conduct a detailed analysis of one robot arm, resulting in an in‐depth understanding of the forward kinematics for that particular robot.…”
Section: Existing Forward Kinematics Educational Softwarementioning
confidence: 99%
“…CBS promotes active learning and motivates learners to perform better because of their involvement in practical experiences related to concrete engineering problems. Additionally, CBS promotes reflective observation of transition processes and phenomena not directly observable by human senses, virtual experiential testing, schema construction, development of models of engineering systems, etc… CBS can also provide the learner with quick feedback throughout the learning process, which can guide them in the achievement of specific goals . However, some research studies reported in academic literature have found that CBS does not always enhance learning.…”
Section: Introductionmentioning
confidence: 99%